2019
DOI: 10.1371/journal.pone.0215053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking status, history and intensity on heart rate variability in the general population: The CHRIS study

Abstract: Background Heart rate variability (HRV) reflects the autonomous nervous system modulation on heart rate and is associated with several pathologies, including cardiac mortality. While mechanistic studies show that smoking is associated with lower HRV, population-based studies present conflicting results. Methods We assessed the mutual effects of active smoking status, cumulative smoking history, and current smoking intensity, on HRV among 4751 adults from the Cooperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 40 publications
2
33
0
Order By: Relevance
“…These changes are suggestive of increased sympathetic nervous system activity. The results are in line with those of Murgia [ 22 ] who also observed decreased HRV, with a stronger correlation between SDNN and TP with every 5 pack-year increase and dose-response reductions in SDNN, RMSSD, TP, LF, and HF.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These changes are suggestive of increased sympathetic nervous system activity. The results are in line with those of Murgia [ 22 ] who also observed decreased HRV, with a stronger correlation between SDNN and TP with every 5 pack-year increase and dose-response reductions in SDNN, RMSSD, TP, LF, and HF.…”
Section: Discussionsupporting
confidence: 92%
“…In 2005, Kobayashi [ 21 ] found that LF/HF is significantly increased immediately after smoking. Since these influences may have affected the results of some earlier studies that included people who smoked shortly before the autonomic test, several other papers have attempted to quantify ANS in smokers after a few hours of abstinence [ 22 , 23 ]. Yet, these studies yielded conflicting results and were difficult to interpret in light of comorbidities [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite experimental studies showing negative effects of smoking on changes in HRV, population-based studies show conflicting results. Recently, a population-based epidemiological study reported that heavier smoking intensity was gradually detrimental to HRV, while smoking cessation increased HRV levels, suggesting that heavy smoking is an independent risk factor for a systemic dysautonomic effect (82). In addition, tobacco cigarette smoking has a negative influence on physiological responses and exercise performance, characterized by a significantly attenuated exercise-induced HR response and altered HRV (83).…”
Section: Quitting Smokingmentioning
confidence: 99%
“…Low-frequency (LF) power mainly reflects the sympathetic tone, whereas high-frequency (HF) power correlates more with the parasympathetic tone [ 40 ]. HRV is also significantly influenced by sex, age, physical fitness, clinical comorbidities, smoking and medication [ 41–44 ]. Additional factors linked to decreased HRV are metabolic (diabetes, early stages of glucose intolerance and metabolic syndrome), endocrine (cortisol) and barometric (orthostatic) [ 45–47 ].…”
Section: Introductionmentioning
confidence: 99%